FACTORS THAT CONTRIBUTE TO CHALLENGES ENCOUNTERED BY ENGINEERING LECTURERS AS THEY TEACH VOCATIONAL SUBJECTS IN TVET COLLEGES - Mabunda, Nduvazi Obert; Makgato, Moses; Hondonga, Jerald (Prodi Administrasi Pendidikan Program Pascasarjana Universitas Riau, 2024)
Economic prosperity of any country is heavily reliant on the knowledgeable and skilled graduates produced by the TVET colleges. Eventually, these graduates are expected to be absorbed by the industry and corporate business. There must be adequate support structures for training students in skills by lecturers as TVET colleges are preparatory grounds for skills. Several challenges encountered by engineering lecturers leading to a high failure rate and hampering the aspirations of the country have been observed. To close that gap, this study investigated those factors that contribute to challenges encountered by engineering lecturers as they teach vocational subjects in the Report 191 programmes of TVET colleges. The study only focused on lecturers teaching Report 191 engineering subjects because of the low output in their specific learning areas. Scaffolding Theory guided the study with links towards training of lecturers for institutional development and improved outcomes. Data collection process was in two folds and was collected through observations (n=12) and semi-structured interviews (n=24) from identified lecturers in three different TVET colleges. Preliminary findings suggested that current Report 191 engineering lecturers experience teaching challenges in delivering vocational subjects which is a determinant to the overall students’ pass rate and progression. Evidence of lack of planning and disorderliness; incorrect teaching and learning techniques and inadequate understanding